Analysis on the removal of emerging contaminant from aqueous solution using biochar derived from soap nut seeds. (15th October 2021) - Velusamy, Karthik; Periyasamy, Selvakumar; Kumar, Ponnusamy Senthil; Jayaraj, Thanikachalam; Krishnasamy, Rajasekaran; Sindhu, Jaisankar; Sneka, Dhanabal; Subhashini, Balakrishnan; Vo, Dai-Viet Nguyen
Abstract: For clearing pollutants and emerging contaminants like ciprofloxacin-500mg from wastewaters generated from pharmaceutical industries, soapnut seeds biochar was synthesized and used as an adsorbent for the effective removal process. Tubular furnace operated under nitrogen gas environment was used to synthesize biochar. The batch analysis were carried out successfully to study the removal mechanism and the removal efficiency of the chosen pollutant. The soapnut seeds biochar showed excellent adsorption of ciprofloxacin at pH 6 and temperature 303 K when the dosage was 0.07 g. The Langmuir removal capacity of 33.44 mg/g was received and the Freundlich model provided the best-fits. The ciprofloxacin-500mg adsorption process correlated well with the pseudo-second-order kinetics equation, and the intraparticle diffusion mechanism mainly controlled the process. The characterization of biochar concluded that O–H groups, CO groups, COO − groups and C–F groups, and π-π interactions, pore-filling effect, and cation exchange interactions played a role in the adsorption process. Therefore, the findings of the present work revealed that soapnut seeds biochar would be an excellent low-cost adsorbent for the removal of ciprofloxacin-500mg from wastewater. Graphical abstract: Image 1 Highlights: Newly prepared soapnut seeds biochar showed excellent adsorption activity. It showed the Langmuir maximum adsorption capacity of 33.44 mg/g. The adsorption process correlated well with pseudo-second-order kinetics. Functional groups of soapnut seeds biochar significantly improved pollutant removal.